Stroke Prevention in Clinical Practice - Baker, Daryll M. (Springer London : Imprint: Springer, 2008)
Comprised of short chapters written in a succinct and bulleted style, with clear diagrams and figures to illustrate where appropriate, Stroke Prevention in Clinical Practice is ideal for the busy doctor looking for a comprehensive pocket-sized guide to the everyday management of transient ischaemic attacks (TIAs) and strokes. Strokes are the major cause of disability in the UK, and also the third biggest killer, but awareness and active intervention can prevent the dangers of strokes especially in high-risk groups. By starting with an explanation of TIAs, which so often preceed strokes, this work aims to make more physicians aware of the treatment regimens necessary to manage TIAs. It is vital to be aware of the early signs of TIAs, and be able to recognise them as soon as possible since a considerable amount of stroke prevention treatment stems from knowing the warning signs and taking action. This book discusses how to accurately diagnose the leading causes of strokes, and offers comprehensive treatment advice to avoid future recurrences, with all chapters written by leading experts in the field.